Research progress of auricular point therapy to relieve preoperative period anxiety before elective surgery in adults (耳穴压豆缓解成年人择期手术术前焦虑的研究进展) - GAO Yuan (高原); XU Lingzhi (徐凌志); LI Suxia (李素霞) (中西医结合护理)
Globally, preoperative period anxiety is a common occurrence among adults undergoing elective surgery. Not only can preoperative anxiety lead to delays or cancellations of surgical procedures, but it can also negatively impact the prognosis of the condition being treated. To alleviate this issue, non-pharmacological interventions such as prayer, massage, music, imagery, and acupuncture have been widely employed. These methods have proven effective in reducing preoperative anxiety, lowering healthcare costs, and enhancing patient satisfaction. In particular, the traditional Chinese medicine technique of auricular acupressure offers a novel approach to managing preoperative anxiety through its ability to promote circulation, relieve pain, calm the mind, and induce tranquility. However, current research on auricular acupressure primarily focuses on postoperative scenarios, specific diseases, or types of surgery. Through literature review and analysis, this paper summarizes the application of auricular acupressure in alleviating preoperative anxiety among adults undergoing elective surgery and discusses its physiological mechanisms, providing a reference for clinical practice. Although auricular acupressure presents an effective non-pharmacological intervention, further research is needed to validate its efficacy in clinical settings, and attention must be paid to the risk of infection during its application. (全球范围内, 成年人在择期手术前普遍存在术前焦虑。术前焦虑不仅可能导致手术推迟或取消, 还可能影响疾病的预后。为了缓解这一情况, 非药物干预方法如祈祷、按摩、音乐、图像和针灸等被广泛应用, 这些方法能有效减轻术前焦虑, 降低医疗成本, 提高患者满意度。中医的耳穴压豆疗法, 通过行气活血止痛、宁心安神、镇静等效果, 为术前焦虑的管理提供了新的思路。然而, 目前关于耳穴压豆的研究主要集中在术后, 特定疾病或手术类型上。通过文献检索和分析, 本文总结了耳穴压豆在成年人择期手术中缓解术前焦虑的应用情况, 并探讨了潜在生理机制, 为临床实践提供了参考。尽管耳穴压豆为非药物干预提供了一种有效的手段, 但在临床应用中还需进一步地究验证其效果, 并注意操作中的感染风险。)